A new scoring system for early diagnosis of ventilator-associated pneumonia: LUPPIS - BİLGİLİ, BELİZ; BİLGİN, HÜSEYİN; DURMUŞOĞLU, LÜTFİYE (TERMEDIA PUBLISHING HOUSE LTD, 2020)
Introduction: The Clinical Pulmonary Infection Score (CPIS) based on chest X-ray has been developed to facilitate clinical diagnosis of ventilator-associated pneumonia (VAP); however, this scoring system has a low diagnostic performance. We developed the Lung Ultrasound and Pentraxin-3 Pulmonary Infection Score (LUPPIS) for early diagnosis of VAP and evaluated the performance of this new scoring system. Material and methods: In a prospective study of 78 patients with suspected VAP, we assessed the detection accuracy of LUPPIS for pneumonia in adult patients. We also evaluated the diagnostic performance of pentraxin-3 (PTX-3) findings of infection. On the day of the study, lung ultrasound was performed, PTX-3 levels were determined, and an endotracheal aspirate was obtained for Gram staining and culture. Results: No significant differences were found between groups with respect to age, mechanical ventilation time, APACHE II score, or SOFA score (p > 0.05). Procalcitonin and PTX-3 levels were significantly higher in the VAP (+) group (p < 0.001 and p < 0.001, respectively). The threshold for LUPPIS in differentiating VAP (+) patients from VAP (-) patients was > 7. In predicting VAP, LUPPIS > 7 (sensitivity of 84%, specificity of 87.7%) was superior to CPIS > 6 (sensitivity of 40.1%, specificity of 84.5%). Conclusions: LUPPIS appears to provide better results in the prediction of VAP compared to CPIS, and the importance of lung ultrasound and PTX-3 is emphasized, which is a distinctive property of LUPPIS.
Keywords: ventilator-associated pneumonia; Clinical Pulmonary Infection Score; lung ultrasound; pentraxin-3; C-REACTIVE PROTEIN; LONG PENTRAXIN PTX3; ATTRIBUTABLE MORTALITY; CHEST RADIOGRAPHY; ULTRASOUND ASSESSMENT; LUNG ULTRASOUND; RECOGNITION; INFECTIONS; BIOMARKERS; GUIDELINES